Pengaruh Sosial Media Dalam Meningkatan Kemampuan Siswa Dalam Membedakan Bahasa Baku Dan Bahasa Tidak Baku Berdasarkan EYD - Parulian Sibuea; Igra Ananda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The ability to differentiate between standard and non-standard language is one of the lessons that must be studied in Indonesian. This research aims to examine the effectiveness of social media in improving students' ability to differentiate standard language from non-standard language based on EYD. The method used is a literature study by examining in depth the EYD guidelines published by the Language Development and Development Agency, as well as analyzing journals and scientific articles related to the influence of social media on students' ability to differentiate between standard and non-standard languages. The results of the study show how much social media influences students' ability to differentiate standard language from non-standard language based on EYD.